2020
DOI: 10.1002/pbc.28679
|View full text |Cite
|
Sign up to set email alerts
|

Composite sarcoma of bone with focal rhabdomyosarcoma and lymph node metastasis in an adolescent

Abstract: Composite sarcoma of bone is a very rare entity that primarily affects adolescent and young adult patients. It usually combines areas of liposarcoma and osteosarcoma, and up to 60% of cases have metastatic disease at diagnosis. It is a highly aggressive pathology with intrinsic resistance to bone sarcoma conventional treatments. The prognosis is poor, with long-term survival rates not exceeding 30%. We present the case of an adolescent female diagnosed with an aggressive composite sarcoma of bone with rhabdomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Second, the ROR results for the drugs in the combined medications, like ifosfamide, etoposide, everolimus, etc., were much lower when the above method was used to calculate them than the former. The existing literature confirmed that sarcoma usually metastasizes with a stable frequency, most children treated with VEGFR-TKI are already advanced, and lung metastases are more likely (Burnei et al, 2013;Interiano et al, 2015;Murugan et al, 2018;Andión Catalán et al, 2020). Considering the data from FAERS depends on spontaneous reporting, a significant bias would be presented after correlating the presence or not of metastases from sarcoma with the occurrence of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the ROR results for the drugs in the combined medications, like ifosfamide, etoposide, everolimus, etc., were much lower when the above method was used to calculate them than the former. The existing literature confirmed that sarcoma usually metastasizes with a stable frequency, most children treated with VEGFR-TKI are already advanced, and lung metastases are more likely (Burnei et al, 2013;Interiano et al, 2015;Murugan et al, 2018;Andión Catalán et al, 2020). Considering the data from FAERS depends on spontaneous reporting, a significant bias would be presented after correlating the presence or not of metastases from sarcoma with the occurrence of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%